A simplified approach for the ultimate limit state analysis of three-dimensional reinforced concrete elements. (15th September 2016) - Meléndez, Carlos; Miguel, Pedro F.; Pallarés, Luis
Highlights: Simplified comprehensible 3D constitutive model for concrete. Ultimate limit state analysis of 3D reinforced concrete elements. Unites accuracy and adaptability of finite elements and simplicity of design methods. Numerical analysis of pile caps and socket base column-to-foundation connections. Viewing the three-dimensional flow of forces. Abstract: Several advanced constitutive models of concrete have been developed in recent decades, some of which are able to reproduce the behaviour of concrete structures with a high level of accuracy. Yet given their complex formulation, their application by most practitioners can entail some difficulties. This paper describes the adoption of an alternative, simplified comprehensible constitutive model for the ultimate limit state analysis of 3D reinforced concrete structural elements. The proposed model is described and the undertaken assumptions are justified. Different uniaxial stress–strain models can be adopted, particularly neglecting the tensile strength of concrete permits to study the goodness of the stress field method and the strut-and-tie method for 3D elements. This model was implemented into a non-linear finite element-based tool developed by the authors. The results of twelve four-pile caps and three socket base column-to-foundation connections are shown. The proposed approach facilitated the identification of the flow of forces and allowed a better understanding of the structural response.